Analisis Pengaruh Budaya Organisasi, Keterikatan Karyawan, dan Lingkungan Kerja Terhadap Kepuasan Karyawan dan Kinerja Karyawan di PT. XYZ Menggunakan Metode Partial Least Square (PLS) - Shiamia Narendra Destariza Ibniadji; Minto Waluyo (Pusat Riset dan Inovasi Nasional, 2023)
Human resources or labor are important assets for a company. Effective human resource management can create an optimal work environment to increase workforce productivity in the company. The purpose of this research is to analyze the influence of the work environment, organizational culture, and employee engagement on job satisfaction and performance in production department employees at PT. XYZ uses the Partial Least Square (PLS) method. PT. XYZ is a pioneer company in marine equipment and maritime services located in Surabaya, East Java. The research results show that organizational culture has a positive and significant effect on employee satisfaction, employee engagement has a positive and significant effect on employee satisfaction, the work environment has a negative and insignificant effect on employee satisfaction, and employee satisfaction has a positive and significant effect on employee performance